Cd-doping effects in Ni–Mn–Sn: experiment and ab-initio study. (23rd June 2022) - Ghazinezhad, Z; Kameli, P; Ghotbi Varzaneh, A; Sarsari, I Abdolhosseini; Norouzi-Inallu, M; Amiri, T; Salazar, D; Rodríguez-Crespo, B; Vashaee, D; Etsell, T H; Chernenko, V
Abstract: Martensitic transformation (MT), magnetic properties, and magnetocaloric effect (MCE) in Heusler-type Ni47 Mn40 Sn13− x Cd x ( x = 0, 0.75, 1, 1.25 at. %) metamagnetic shape memory alloys (MetaMSMAs) are investigated, both experimentally and theoretically, as a function of doping with Cd. Ab-initio computations reveal that the ferromagnetic (FM) configuration is energetically more favorable in the cubic phase than the antiferromagnetic (AFM) state in undoped and doped alloys as well. Moreover, it is revealed that the alloys in the ground state exhibit a tetragonal structure confirming the existence of MT, in agreement with the experiments. It was indicated, both in theory and practice, that a reduction of the unit cell volume and an increase of the MT temperature as a function of the Cd doping. Indirect estimations of MCE in the vicinity of MT were carried out by using thermomagnetization curves measured under different magnetic fields up to 5 T. The results demonstrated that the doped alloys exhibit enhanced values of the inverse MCE comparable with those of Ni-Mn-based MetaMSMAs. Maximum magnetic entropy change in a field change of 2 T increases from 3.0 J .k g − 1 K − 1 for the undoped alloy to 3.4 and 5.0 J .k g − 1 K − 1 for the alloys doped with 0.75 and 1 at.% of Cd, respectively. The inverse and conventional MCE were explored by direct measurements of the adiabatic temperature change under the magnetic field change of 1.96 T. The Cd doping increased the maximum of inverse MCE by nearly 78% from 0.9 K to 1.6 K for the undoped and doped alloys, respectively. The results depicted that Cd doping can effectively tailor the structural, magnetic, and MCE properties of the Ni–Mn–Sn MetaMSMAs.